LISA: Surfactant administration in spontaneous breathing. Which evidence from the literature? - Lista, G.; La Verde, A.; Castoldi, F. (Acta Biomedica Atenei Parmensis, 2015)
Recent human and animal studies demonstrated that surfactant can be delivered intratracheally without traditional intubation and bagging, but using a fine catheter inserted into the trachea of spontaneously breathing preterm infants on CPAP. This strategy, known as LISA (less invasive surfactant administration) or MIST (minimal invasive surfactant therapy), seems to reduce failure of non-invasive respiratory approach. Avoiding mechanical ventilation and manual inflation it is possible to reduce lung injury due to baro-volutrauma. Moreover leaving the infants supported by N-CPAP during the maneuver, it is possible to reduce the risk of lung derecruitment. Further studies are needed to confirm the promising effects due to this strategy to deliver surfactant.